A Case Study on Integrating First Language (L1) to English as a Second Language Classroom for Vocabulary Enhancement and Comprehension Augmentation. - Douglas, S. (Department of Linguistics, University of Kelaniya, Sri Lanka., 2017)
The debate of including or excluding the students‟ native language to an English as a second language classrooms has been a contentious issue for a long time. There is a need to experiment this issue and investigate the direct impact of mother tongue in the second language classroom. The aim of this study is to identify the impact of using a limited amount of first language (L1) in the second language class room for vocabulary enhancement and comprehension augmentation and its variation across proficiency levels. The study was conducted at Vavuniya Tamil Madhya Maha Vidyalayam with sixty-six Advanced Level students. They were divided into experimental and controlled groups. A pre-test was conducted to recognize the vocabulary and comprehension levels of the students. Subsequently, a reading comprehension session was conducted using the Direct Method for the controlled group. The experimental group attended the session in Principled Eclectic Method. The post-tests were followed and the data were statistically analyzed to identify the impact by paying individual attention to participants‟ proficiency levels and question types. The mean marks of the experimental group in the pre-test is 46.79 and the standard deviation is 29.27. In the post-test, there is a remarkable improvement in the result of the experimental group showing 57.88 and the standard deviation 28.50. The findings confirm that the impact of using L1 differs according to the individual student‟s proficiency where little impact was observed in high proficiency learners while a remarkable impact was observed in intermediate learners. However, the study concludes that there is a fairly high impact in using a limited amount of L1 in the ESL classroom for vocabulary enhancement and comprehension augmentation in facilitating the learners‟ language development.
Keywords: Comprehension Augmentation; First Language; Impact; Integration; Vocabulary Enhancement